Digital resilience: Understanding the influence of social media and support networks on university students' isolation during COVID-19 - Surya, Yuyun Wahyu Izzati; Mazahir, Ibtesam; Yaseen, Safeena; Wibowo, Nimas Safira Widhiasti (Faculty of Social and Political Science, Universitas Airlangga, 2024)
The global COVID-19 pandemic has led to widespread social isolation measures, potentially exacerbating mental health issues, especially among young adults. This demographic, known for its high social media usage, faces increased risk of negative mental health outcomes such as isolation and depression. This study explores how social media engagement and social support seeking mediate the relationship between age and social isolation symptoms during the pandemic. Using a qualitative research methodology, data was collected from twenty university students in Pakistan through semi-structured interviews. The interviews delved into various aspects including depressive symptoms, loneliness, coping mechanisms, and changes in daily routines due to the pandemic. The analysis reveals that university students experienced greater levels of loneliness compared to older age groups. Additionally, they exhibited increased use of social media platforms while seeking less social support. These findings highlight the mental health implications of fear and isolation during a global pandemic, both in Pakistan and in other countries. The study underscores the importance of targeted interventions to address the mental well-being of young adults during and after the COVID-19 crisis.